Análise genética de características de crescimento e de resistência a parasitos em bovinos Nelore por meio de regressão aleatória - Tiago Luciano Passafaro (2014)
This work aimed to identify random regression models for genetic evaluation of weight and resistance to tick, gastrointestinal nematodes and Eimeria spp. in Nellore cattle, using Legendre polynomials and bayesian inference. The databases contained 63,880, 4,270, 3,872 and 3,872 records of body weight and resistance to tick, gastrointestinal nematodes and Eimeria spp. of 12,260, 1,188, 1,142 and 1,142 Nellore calves, respectively, from 146 to 597 days of age. The relationship matrix contained 15,927 animals. The models included the fixed effects of contemporary groups and the population mean trend for each trait, and age of dam at calving (linear and quadratic) and age of calf on weighing (linear) for body weight. The direct genetic additive, permanent environmental and residual effects were included in each model for all traits. In body weight analyses the maternal genetic additive and maternal permanent environment effects were also included. The residual variance for body weight was fitted into classes of age, and the models with one, four and eight classes were assessed. The best-fitting model for weight considered third order polynomial to fit the population mean trend, fourth order polynomial for direct additive, and fifth order polynomials for the remaining random effects, and eight classes of age for residual variance. For resistance traits, the best-fitting models considered linear polynomial for population mean trend and all random effects, except for the population mean trend of resistance to Eimeria spp., which was fitted by a third order polynomial. The posterior mean of direct heritability were low to high and ranged from 0.18 to 0.58, 0.07 to 0.38, 0.02 to 0.34 and from 0.04 to 0.39, for body weight, resistance to tick, gastrointestinal nematodes and Eimeria spp., respectively. The posterior mean of correlations for each random effect for body weight were positive with low to high magnitude between the pair of ages 205, 365 and 550 days. The posterior mean of genetic and environmental correlations between the pair of ages 205, 365, 450 and 550 days for the same resistance trait were favorable for closed ages and unfavorable for distant ages. In general, the posterior mean of genetic and environmental correlations between resistance traits were low and the high density intervals with 95% (HDI95%) of samples were large and included the zero in many cases. Exception for the genetic correlation between resistance to nematodes and Eimeria spp. which were high and the HDI95% did not contain zero. There was enough additive genetic variability for all traits and genetic progress can be achieved over generations through selection.